1989
DOI: 10.1007/bf01871941
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of MgATP-Driven H+ uptake in to a microsomal vesicle franction from rat pancreatic acinar cells

Abstract: In microsomal vesicles, as isolated from exocrine pancreas cells, MgATP-driven H+ transport was evaluated by measuring H+-dependent accumulation of acridine orange (AO). Active H+ uptake showed an absolute requirement for ATP with simple Michaelis-Menten kinetics (Km for ATP 0.43 mmol/liter) with a Hill coefficient of 0.99. H+ transport was maximal at an external pH of 6.7, generating an intravesicular pH of 4.8. MgATP-dependent H+ accumulation was abolished by protonophores, such as nigericin (10(-6) mol/lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 45 publications
(43 reference statements)
1
23
0
Order By: Relevance
“…3 Lower, lanes 3 and 5). Subfractionation of the vesicle preparation by Percoll gradient centrifugation (8) (15,16) or with the electrogenic protonophore CCCP. In the presence of bafilomycin B1 (10 nM) or CCCP (10 ,uM), the MgATP-dependent H+ uptake was abolished (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…3 Lower, lanes 3 and 5). Subfractionation of the vesicle preparation by Percoll gradient centrifugation (8) (15,16) or with the electrogenic protonophore CCCP. In the presence of bafilomycin B1 (10 nM) or CCCP (10 ,uM), the MgATP-dependent H+ uptake was abolished (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The ADP-ribosylation factor (ARF), a highly conserved low molecular weight GTPbinding protein, has been located in the Golgi complex and implicated to function in intracellular protein transport from the endoplasmic reticulum to and within the Golgi complex (5,6). A monoclonal anti-ARF antibody has been used to detect the ARF protein in a vesicle preparation of rat pancreatic acinar cells containing membranes ofthe endoplasmic reticulum and the Golgi complex (7,8). By immunoelectron microscopy with the same antibody, ARF staining in pancreatic acinar cells was shown to be confined to the cytoplasmic faces of trans-Golgi stack membranes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Schultz and coworkers [287,2881 have recently suggested that Ca2+ accumulation by the Ins(l,4,5)P3-sensitive store does not depend on the activity of a Caz+-ATPase, but rather on a more complicated mechanism involving first the formation of a pH gradient (acidic interior), due to a H+-ATPase and subsequently an electro-neutral exchange of 2 H ' ,'Ca2+.…”
Section: A 2 + / 2 H' Exchangermentioning
confidence: 99%